Leishmania infection and neuroinflammation: Specific chemokine profile and absence of parasites in the brain of naturally-infected dogs - Melo, Guilherme D. [UNESP]; Silva, José Eduardo S. [UNESP]; Grano, Fernanda G. [UNESP]; Souza, Milena S. [UNESP]; Machado, Gisele F. [UNESP] (Elsevier, 2015)
Visceral leishmaniasis is a chronic disease caused by Leishmania infantum. We aimed to detect the parasite in the brain of fifteen naturally-infected dogs using in situ hybridization and immunohistochemistry, and the gene expression of selected chemokines by RT-qPCR. We detected no parasite in the brain, but perivascular deposition of parasite DNA and IgG in the choroid plexus. We noticed up-regulation of CCL-3, CCL-4 and CCL-5, coherent with T lymphocyte accumulation, stating the brain as a pro-inflammatory environment. Indeed, not necessarily the parasite itself, but rather its DNA seems to act as a trigger to promote brain inflammation during visceral leishmaniasis.
Keywords: Central nervous system; Chemokine CCL3; Chemokine CCL4; Chemokine CCL5; T lymphocytes; Visceral leishmaniasis